Prototype Robot for Computer Vision and Control Systems Applications - Masetti, Augusto (2017)
This paper describes a robot designed and developed by a student in the context of an Electronic Engineering degree course. This robot is composed by three wheels, two of them can be controlled inde- pendently and the third one is used for stability. The robot also includes a webcam provided with pan and tilt control. This work was focused on the implementation of a prototype useful for academic research in the areas of Computer Vision and Control Systems Dynamics. In this document, the main characteristics of this robot are described.